COMMUNITY EMPOWERMENT THROUGH TRAINING IN APPLICATION OF CODEIGNITER FRAMEWORK TEMPLATE IN WEB-BASED APPLICATION PROGRAMMING - Rian Cahyadi,; Alya Nurul Aulia,; Aulia, Alfitriani; Wiwin Herwina, (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Technological developments are growing rapidly and have brought many benefits to mankind. Its presence can alleviate all the difficulties that arise in work and human activities. Technological developments also open up employment opportunities, especially in today's digital era, many startups need jobs to create and develop a technology, just like the programmer profession. This community empowerment program through training aims to equip job seekers to have skills in applying bootstrap templates to a website in order to simplify the website design process. This program was implemented at the Tasikmalaya City Manpower Office on Thursday, October 13, 2022 with the target of fresh graduate job seekers, unfamiliar with programming, and having the desire to learn about programming in Tasikmalaya City. The curriculum used for this program is based on the standard curriculum contained in the SKKNI, namely Installing Programming Software Tools. The stages carried out are preparation, introduction, delivery of sub-topics, conclusions, applications, evaluations, additional assignments, and class arrangements. The approach used is an andragogic approach with direct learning strategies (Direct Instruction) with lecture, demonstration, practice and discussion/question and answer methods with an inductive learning model centered on the trainees (student centered learning). The evaluation process on empowerment is carried out through interview and observation techniques.